Efeito do sildenafil em modelo colinérgico de convulsão em camundongos e de estresse In vitro: abordagem comportamental e neuroquímica - Carvalho, Michele Albuquerque Jales de (2016)
Seizures are the transient behavior changes resulting from rhythmic outbreaks, synchronic and disordered populations of brain neurons. Sildenafil is a selective inhibitor of PDE5 which enhances erectile function due to increased cytoplasmic levels of cGMP. Some experimental studies and case reports suggest that sildenafil may exert pro convulsive activity. This work aimed to study the effects of sildenafil on seizure pilocarpine model in mice and on the viability of astrocytes in vitro before the cholinergic stress. Swiss male mice (25-34g) were pre-treated with sildenafil (2.5, 5,. 10 or 20mg / kg, ip, n = 8) and in acute treatment for 7 days. Half an hour after the last dose of sildenafil convulsion was induced in all animals by the administration of pilocarpine 400 mg / kg, ip. (P400). In behavioral analysis, the time to occurrence of the first seizure and death after the tests were dissected three brain areas were recorded (pre-frontal cortex, hippocampus and striatum) to determine the activity of acetylcholinesterase, the degree of lipid peroxidation, by measuring the concentration of malondialdehyde (MDA), the concentration of nitrite and also the participation of glutathione reductase antioxidant defense (GSH). In vitro assay, cell viability was determined cortical astrocytes after treatment with different concentrations of Sildenafil + pilocarpine. Data were analyzed by ANOVA and Student-Newman-Keuls test and post-test, for in vivo tests and ANOVA followed by Bonferroni post-test, for in vitro experiments. It was observed that sildenafil reduced the latency of convulsions and death at doses of 10 and 20 mg / kg in both acute pretreatment such as 7 days. Regarding the parameters of oxidative stress and antioxidant defense, an increase of MDA levels in all areas at doses of 10 and 20 mg / kg in the acute pretreatment, whereas in pretreatment for 7 days there were increasing levels of MDA in the prefrontal cortex at the dose of 20 mg / kg and the hippocampus in the dose of 10 and 20 mg / kg. The nitrite concentration was increased at doses of 10 and 20 mg / kg in the prefrontal cortex and hippocampus in doses of 10 and 20 mg / kg and in the striatum at a dose of 20 mg / kg pre-treatment for 7 days, and in acute pretreatment was increased in the frontal cortex pre dose of 20 mg / kg and in the striatum at a dose of 10mg / kg. Regarding the reduced glutathione did not change in group pretreated with sildenafil compared to P400 + P400 group. The combined treatment of sildenafil (1000, 500, 250, 125, 75, 37 ug / ml) and pilocarpine (IC 50 - Cytotoxicity index to 50% of the cell population study corresponding to 31.83 mM) caused a reduction in viability cells only in the concentration of 1000 ug / mL, suggesting that astrocytes can be involved in the possible neurotoxicity of sildenafil in the convulsive process, requiring further studies.. Our findings suggest sildenafil has a proconvulsivant activity related to cholinergic mechanisms and demonstre oxidizing action in the highest doses studied.